Challenges in the Management of Hypertrophic Pyloric Stenosis in a Malnourished Infant with Pulmonary Tuberculosis: A Case Report - Basri Hadi; Yusri Dianne Jurnalis; Mayetti Akmal; Didik Hariyanto; Yuanico Lirauka (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Hypertrophic pyloric stenosis (HPS) is a common cause of gastric outlet obstruction in infants, but its management can be challenging in the presence of comorbidities like malnutrition and pulmonary tuberculosis (PTB). This case report highlights the complexities and considerations in managing an infant with HPS, PTB, and severe malnutrition. Case presentation: A 6-month-old male infant presented with lethargy, recurrent vomiting, and failure to thrive. He had a history of PTB on anti-tuberculosis treatment and was severely malnourished. Investigations revealed HPS, and he underwent a pyloromyotomy. Postoperatively, he required careful fluid management, nutritional support, and continued anti-tuberculosis therapy. Conclusion: This case highlights the challenges in managing HPS in an infant with PTB and severe malnutrition. It underscores the importance of a multidisciplinary approach involving pediatricians, surgeons, and nutritionists to ensure optimal outcomes in such complex cases.